Assessing genetic redundancy and diversity in Colombian cacao germplasm banks using SNP fingerprinting - Osorio-Guarín, Jaime A.; Berdugo-Cely, Jhon A.; Garzón-Martínez, Gina A.; Toloza-Moreno, Deisy Lisseth; Delgadillo-Duran, Paola; Báez-Daza, Eliana Y.; Meinhardt, Lyndel W.; Park, Sunchung; Zhang, Dapeng; Yockteng, Roxana (Frontiers in Plant Science, 2025)
Cacao germplasm is the cornerstone of sustainable cacao production, underpinning efforts to develop high-yielding, quality-rich, and climate-resilient varieties. This study aimed to evaluate the mislabeling, the genetic redundancy, and diversity of two cacao germplasm banks maintained at the Palmira and La Suiza research centers of the Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA), from Colombia. We genotyped 4,653 cacao trees from these collections, and after applying quality control filters, a final set of 77 SNP markers was used for all subsequent analyses. Our results revealed that both collections exhibit a similar pattern of genetic diversity. However, a medium rate of mislabeling (12.4%) and high genetic redundancy (53.1%) were detected, likely due to errors in collecting, introduction, pre-planting labeling, and the use of rootstocks. To optimize the evaluation conserved cacao germplasm, we defined core collections independently, which comprise 246 and 190 samples for Palmira and La Suiza, respectively. This research demonstrates the importance of maintaining a well-classified cacao collection with minimal genetic redundancy, thereby improving accuracy and reducing maintenance costs. This will not only enhance conservation efforts but also enrich the genetic diversity of the collection.